2007
DOI: 10.1111/j.1479-8425.2007.00318.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a sleep hygiene education program on the sleep?wake cycle of Brazilian adolescent students

Abstract: Adolescents present with sleep timing delay, irregular sleep-wake (SW) schedules and short sleep duration (<7 h) on school days, all resulting from biological and behavioral factors. To minimize this, we evaluated the effect of a school-based sleep hygiene program on the SW cycle, sleep quality and sleepiness in 58 Brazilian adolescent students. The sleep hygiene program lasted a week and consisted of a daily 50 min activity, such as a sleep physiology class, constructing a sleep ontogeny map, discussing the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
99
2
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(116 citation statements)
references
References 39 publications
5
99
2
2
Order By: Relevance
“…Although all studies reported delivering at least basic knowledge about sleep physiology and/or sleep hygiene, the scope and aims of the programs fell into one of two groups; those who sought solely to disseminate information and improve sleep knowledge, 21,[23][24][25] and those who sought to actively change sleep behavior. [17][18][19][20]22,[26][27][28] Seven themes that were identified from the studies are listed below in no particular order:…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Although all studies reported delivering at least basic knowledge about sleep physiology and/or sleep hygiene, the scope and aims of the programs fell into one of two groups; those who sought solely to disseminate information and improve sleep knowledge, 21,[23][24][25] and those who sought to actively change sleep behavior. [17][18][19][20]22,[26][27][28] Seven themes that were identified from the studies are listed below in no particular order:…”
Section: Resultsmentioning
confidence: 99%
“…Most studies utilized written documentation in classrooms in combination with didactic teaching modules. [17][18][19][20][22][23][24][25][26][27][28]30 Although all studies showed improvements in sleep knowledge through these methods, many studies reported that students preferred more interactive activities rather than traditional didactic methods. 17,23,26 Indeed, Bakotić et al 21 suggest utilizing graphic designs and interactive sleep activities is more likely to promote interest in the content.…”
Section: Modes Of Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…Although the relation between sleep knowledge and sleep practices is mixed, sleep education remains an essential step in promoting healthy sleep. Indeed, general education interventions targeted at children [118] and parents [119] have yielded promising results.…”
Section: Community/public Health Education and Prevention Of Insomniamentioning
confidence: 99%